Perioperative Anaesthetic Considerations in Neurofibromatosis Type 1 with Periampullary Neuroendocrine Tumour Undergoing Whipple’s Procedure: A Case Report - Abhigna Gummalla; Vivek Chakole; Bhagyesh Sapkale (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Neurofibromatosis type 1 (NF1) is an autosomal dominant multisystem disorder which is associated with benign and malignant tumours, skeletal deformities, airway lesions as well as endocrine abnormalities such as phaeochromocytoma posing significant anaesthetic challenges. Gastrointestinal involvement usually manifesting as periampullary Neuroendocrine Tumours (NETs), although uncommon may also require major surgical intervention. The present case report describes a 65-year-old male having known NF1 diagnosed with a well-differentiated periampullary NET scheduled for elective pancreaticoduodenectomy. Preoperative evaluation further showed multiple cutaneous, intraoral neurofibromas without any clinical evidence of difficult airway or carcinoid syndrome. Cardiovascular assessment was also unremarkable as well as biochemical parameters were within acceptable limits. Anticipating potential airway and haemodynamic concerns, invasive arterial and central venous monitoring were instituted and combined general anaesthesia along with epidural analgesia was administered. The intraoperative course of the patient remained haemodynamically stable also recovery was uneventful. The case highlights the importance of meticulous preoperative assessment, vigilance for occult endocrine pathology as well as individualised perioperative planning to ensure safe anaesthetic management in NF1 patients who are undergoing major abdominal surgery.